THE SOCIAL IMAGINARY OF EXTREME ADVENTURERS: THE SEARCH FOR VERTIGO (Fiep Bulletin - online, 2011)
Objective: The aim of this study is identifying the senses and meanings that are shown in extreme risk sports practicers' speeches. Methodology: Study with qualitative research approach. As an instrument for data collection, a semi-structured interview applied to 11 Brazilian participants of extreme risk sports was adopted. The method for the speech analysis was the one proposed by Orlandi (2001). Results: Among the imaginary marks that emerged from the speeches, we highlight ecstasy senses revealed by the search for vertigo. Conclusion: As ultra-resistance extreme practices are taken, our informers cultivate exaltation and power feelings, which will keep them throughout the athletic competitions. They engender a vertical effort in their performances, getting far from mortals. They search for the intoxicated vertigo moment which lets them meet exhaustion and the end of their oneiric strenghths, meet death, flert with it, but with the necessity of needing to survive. Good aspects of their souls are developed: audacity, impulse, courage and self-control.
Keywords: social imaginary; adventure and risk sport; vertigo